Critical Discourse Analysis of Positive Narratives About Prabowo Subianto in YouTube Video of Helmy Yahya Berbicara - Widianti, Dwi; Sufyanto, Sufyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study analyzes Helmy Yahya's video entitled